The Effect of Capital Intensity, Inventory Intensity, Company Size and Leverage on Tax Avoidance in the Coal Mining Sector on the Indonesia Stock Exchange 2017 – 2021 - Ghani Arief Sulaiman; Putri Zanufa Sari (NAROTAMA UNIVERSITY, Indonesia, 2023)
This study aims to analyze the influence of Capital Intensity, Inventory Intensity, Company Size and Leverage on Tax Avoidance. This study uses a quantitative approach in the form of financial reports of coal mining companies listed on the Indonesia Stock Exchange from 2017 to 2021. The sampling technique used in this study used a purposive sampling approach, the number of samples used in this study were 55 samples. The results of this study indicate that the results of testing the first hypothesis (H1) show that capital intensity has an effect on tax avoidance, the results of testing the second hypothesis (H2) show that inventory intensity has no effect on tax avoidance, the results of testing the third hypothesis (H3) show that company size has an effect on tax avoidance, the results of testing the fourth hypothesis (H4) show that leverage has an effect on tax avoidance, the results of testing the fifth hypothesis (H5) show that capital intensity, inventory intensity, firm size and leverage simultaneously have an effect on tax avoidance. The problem definition in this study is very important in bringing the subject matter closer so that there is no confusion in interpreting the research results. In this study there are variable restrictions, namely using only independent variables, namely Capital Intensity, Inventory Intensity, Firm Size and Leverage. The dependent variable is tax evasion using secondary data on the coal mining sector for 2017-2021 which is listed on the Indonesia Stock Exchange. The results of this study are expected to provide consideration related to Capital Intensity, Inventory Intensity, Company Size and Leverage on tax avoidance.